Building a Better Future: Strategical Approaches in Tackling Poor Maintenance in Nigerian Public Secondary Schools - Adeoye, Moses Adeleke; Shogbesan, Yusuf Olayinka; Jolaoye, Joshua Durotoye; Abdullateef Hassanat Jimoh (Universitas Pendidikan Ganesha, 2024)
Secondary schools have long been plagued by issues of poor maintenance, resulting in dilapidated infrastructure, limited resources and a subpar learning environment for students. To address this pressing issue, it is crucial to adopt strategic approaches that focus on improving maintenance practices and ensuring the long-term sustainability of these schools. This study aims to analyze the key challenges faced by Nigerian public secondary schools in terms of maintenance and presents innovative solutions that can help build a better future for education in the country. The research method uses Systematic Literature Review (SLR). A literature search was conducted through academic databases, such as PubMed, ERIC, and Google Scholar. It is essential to establish a comprehensive system for monitoring and evaluating the maintenance of public secondary schools. The government should allocate a significant portion of the education budget to address infrastructure maintenance and ensure that funds are properly utilized. This investment will help to improve the physical condition of schools and create a conducive learning environment for students. By involving the community in the maintenance process, a sense of ownership and responsibility can be fostered, leading to better maintenance practices.